Elaboração da base de dados geográficos de Assú-RN com o uso de geotecnologias livres - Carvalho, Felipe Rodolfo da Cunha (Universidade Federal Rural do Semi-Árido, 2020)
Geoprocessing is the set of techniques used for the treatment of spatial information or georeferenced data. These techniques include Cartography, Conventional Topography, Global Positioning System (GPS), Remote Sensing and Geographic Information System (GIS), starting from the use of simple tools and instruments to the use of positioning satellites. However, the use of geoprocessing techniques is difficult to access in terms of cost or difficulty of use. In this context, this work aims to promote the updating of the cartographic base of the municipality of Assú-RN from free data processed in a free GIS environment. Academic works, documents from specific websites and available books that addressed the topic for study were used as a source for analysis. In this way, it was possible to obtain files for mapping in different segments that help the municipality in its urban management. Thus, it was possible to observe that the use of geoprocessing techniques, through free software is feasible and important for obtaining information, enabling the updating of the cartographic database of small cities.
Keywords: Geoprocessamento; Planejamento urbano; SIG´S; Gestão territorial; Geoprocessing; Urban planning; SIG'S; Territorial management; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA